Systematic Review of Extended Reality Digital Therapy for Enhancing Mental Health Among South Korean Adolescents and Young Adults - Lee, Serim; Yoon, Jiyoung; Cho, Yeonjee; Chun, JongSerl (Journal of korean Academy of Child and Adolescent Psychiatry, 2023)
Digital therapy using extended reality (XR) holds great promise for addressing the mental health needs of adolescents and young adults. This study addresses a notable research gap in South Korea by systematically reviewing XR-based digital therapy for the mental health of South Korean adolescents and young adults. We analyzed 26 studies encompassing various aspects, including study type, publication date, research field, research methodology, data sources, program types, program content, sample characteristics, target population, assessment tools, and program effectiveness. Notably, 46.15% of the studies employed an experimental design, whereas over 53% utilized non-experimental approaches. Experimental studies lacked a genuine design, standardized questionnaires, and control variables. Similarly, non-experimental studies failed to report specific literature selection criteria. Consequently, future studies should adopt rigorous methodologies to enhance reliability and validity. Moreover, over 85% of the 26 studies focused solely on virtual reality and did not incorporate augmented or mixed reality. This study identifies the limitations of the previous research. These findings emphasize the need for structured investigations to advance the development of XR-based digital therapy to promote mental health in adolescents and young adults in South Korea.